2020
DOI: 10.1016/j.ymthe.2019.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Increased Microglial Exosomal miR-124-3p Alleviates Neurodegeneration and Improves Cognitive Outcome after rmTBI

Abstract: Repetitive mild traumatic brain injury (rmTBI) is considered to be an important risk factor for long-term neurodegenerative disorders such as Alzheimer's disease, which is characterized by b-amyloid abnormalities and impaired cognitive function. Microglial exosomes have been reported to be involved in the transportation, distribution, and clearance of b-amyloid in Alzheimer's disease. However, their impacts on the development of neurodegeneration after rmTBI are not yet known. The role of miRNAs in microglial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 68 publications
1
120
0
Order By: Relevance
“…In a 2020 study of rTBI, miR-124-3p levels in MDE were found to be significantly altered in the acute, sub-acute, and chronic phases following the injury (180). Intravenous administration of MDE with upregulated miR-124-3p alleviated neurodegeneration in repetitive scratch-injured neurons, the effects of which were exerted by miR-124-3p targeting RelA, an inhibitory transcription factor of apolipoprotein E (ApoE) that promotes β-amyloid proteolytic breakdown, thereby inhibiting β-amyloid abnormalities (180).…”
Section: Microglial Extracellular Vesiclesmentioning
confidence: 98%
“…In a 2020 study of rTBI, miR-124-3p levels in MDE were found to be significantly altered in the acute, sub-acute, and chronic phases following the injury (180). Intravenous administration of MDE with upregulated miR-124-3p alleviated neurodegeneration in repetitive scratch-injured neurons, the effects of which were exerted by miR-124-3p targeting RelA, an inhibitory transcription factor of apolipoprotein E (ApoE) that promotes β-amyloid proteolytic breakdown, thereby inhibiting β-amyloid abnormalities (180).…”
Section: Microglial Extracellular Vesiclesmentioning
confidence: 98%
“…In metabolism and cardiovascular diseases, exosomes induce metabolic disorders in adipocytes and islet cells [66,67]. Exosomes may impair the formation of neurotoxic oligomers and promote neurodegeneration [68][69][70]. More importantly, exosomes are associated with tumor growth, angiogenesis, metastasis, sensitivity to chemotherapy, and immune evasion [47,71,72].…”
Section: The Biosynthesis and Function Of Extracellular Vesicles And mentioning
confidence: 99%
“…EV-mediated delivery of miRNAs is reported to attenuate neurodegeneration and restore cognitive function in a repetitive mild traumatic brain injury (rmTBI) model that simulates aspects of AD (Ge et al, 2020). It is noted that miR-711 has been identified to modulate anti-inflammatory pathways and M2-like activation phenotype, as was demonstrated previously in the context of neuroinflammatory reactions revealed by microarray expression profiling (Freilich et al, 2013).…”
Section: Introductionmentioning
confidence: 62%